Recalling the practice of probation - Aline Vasconcelos Marques; Claudia Cristina A. Da Silva; Marlise Maria Rech; Zenilda Zilda Scalvin (Universidade Federal de Santa Catarina, 2001)
It is in the text show the development of our stage II of Child Education, under the guidance of Professor Cristiana de France Chiaradia.